2015
DOI: 10.1007/s11325-014-1101-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mandibular advancement splint treatment on tongue shape in obstructive sleep apnea

Abstract: This study reports a detailed two-dimensional analysis of tongue dimensions as well as assessment of adjacentsoft palate shape and upper airway structures without and with MAS treatment for OSA. Our finding suggests that MAS does induce changes in tongue shape. MAS treatment responders showed a greater decrease in tongue length (between the tongue tip and hyoid bone) with MAS in situ; whether differences in alteration of tongue position with MAS explain differences in treatment response requires further invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…; Ogawa et al . ). A greater rate of success with oral appliances have been reported among patients with primarily oropharyngeal collapse rather than velopharyngeal collapse (Ng et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Ogawa et al . ). A greater rate of success with oral appliances have been reported among patients with primarily oropharyngeal collapse rather than velopharyngeal collapse (Ng et al .…”
Section: Discussionmentioning
confidence: 97%
“…Magnetic resonance imaging studies have shown that oral appliances induce anterior movement of the tongue base (Brown et al 2013;Ogawa et al 2015). A greater rate of success with oral appliances have been reported among patients with primarily oropharyngeal collapse rather than velopharyngeal collapse (Ng et al 2006;Bosshard et al 2011;Shen et al 2012).…”
Section: Posteriorly-located Tongue and Oral Appliance Therapymentioning
confidence: 99%
“…Several studies have demonstrated increased pharyngeal volume as a result of therapies with MAD using volumetric imaging [3,5,6,[14][15][16][17][18][19][20], but few studies have used this change in the pharynx (MAD in situ and baseline) as a predictor of success, or compare these changes in MAD responders and non-responders.…”
Section: Discussionmentioning
confidence: 99%
“…However,Gao et al (1999) found a positive association between changes in AHI and increased upper oropharynx area after MAD in eleven individuals using magnetic resonance imaging Chan et al (2010). showed increases in size in the upper airway after treatment with MAD only in responders (≄50% reduction in AHI) in 69 individuals using magnetic resonance imaging Ogawa et al (2015). found responders (≄50% reduction in AHI) decreased in relation to tongue length with MAD using magnetic resonance imaging in 68 individuals Lee et al (2010).…”
mentioning
confidence: 99%
“…The key task of this system is to accurately detect the tongue position and record data on the timeline basis. The over time record of intraoral activities is indispensable to adjust physical structure of the device for fitting the requirement of each patient specifically [ 35 , 36 ]. First, the tunneling resistance of a stand-alone sensor array will be characterized by incremental forces.…”
Section: Methodsmentioning
confidence: 99%